2006
DOI: 10.1074/jbc.m511927200
|View full text |Cite
|
Sign up to set email alerts
|

Essential Role of 3′-Untranslated Region-mediated mRNA Decay in Circadian Oscillations of Mouse Period3 mRNA

Abstract: Daily oscillations in mRNA levels are a general feature of most clock genes. Although mRNA oscillations largely depend on transcriptional regulation, it has been suggested that post-transcriptional controls also contribute to mRNA oscillations in Drosophila. Currently, however, there is no direct evidence for post-transcriptional regulation of mammalian clock genes. To investigate the roles of post-transcriptional regulations, we focused on the 3 -untranslated region (3 -UTR) of mouse Period3 (mPer3) mRNA, one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
53
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(53 citation statements)
references
References 36 publications
0
53
0
Order By: Relevance
“…The combination of these two events, induction of transcription and transcript degradation, will result in a sharper peak of CCA1 mRNA accumulation, allowing a more precise detection of early morning, irrespective of seasonal changes. Consistent with the idea that mRNA stability is important for the pattern of oscillator transcript accumulation, experiments carried out in mice have shown that increasing the stability of a chimeric construct based on Period3, an oscillator gene, significantly broadens the peak of expression (Kwak et al, 2006).…”
Section: Discussionmentioning
confidence: 64%
“…The combination of these two events, induction of transcription and transcript degradation, will result in a sharper peak of CCA1 mRNA accumulation, allowing a more precise detection of early morning, irrespective of seasonal changes. Consistent with the idea that mRNA stability is important for the pattern of oscillator transcript accumulation, experiments carried out in mice have shown that increasing the stability of a chimeric construct based on Period3, an oscillator gene, significantly broadens the peak of expression (Kwak et al, 2006).…”
Section: Discussionmentioning
confidence: 64%
“…The circadian oscillation of NIH 3T3 cells was synchronized by treatment with 100 nM dexamethasone. After 2 h, the medium was replaced with complete medium (4,29,46,47). To block the translation system, NIH 3T3 cells were treated with 20 nM rapamycin or 100 g/ml cycloheximide (CHX) and then harvested at the indicated times.…”
Section: Methodsmentioning
confidence: 99%
“…These regulatory steps must be coordinated properly for the fine-tuning of both amplitude and 24-h periodicity. In particular, posttranscriptional regulation plays an important role, although its mechanism is less well understood (17,26,29,46,47). One of the core clock genes in mammals, Period1 (Per1), was originally identified as a structural homologue of the Drosophila melanogaster circadian clock gene per (42).…”
mentioning
confidence: 99%
“…A later study demonstrated that an element in the 3Ј-UTR of Per1 promotes its instability, thereby contributing to this destabilization (Kojima et al, 2003). The 3Ј-UTRs of other clock genes, such as Drosophila Per, rat Aanat, and mouse Per2, Per3 and Cry1, also contribute to regulating their rhythmic expression, thereby leading to an accurate circadian period (Chen et al, 1998;Kim et al, 2005;Kim et al, 2007a;Kwak et al, 2006;Woo et al, 2010;Woo et al, 2009).…”
Section: Post-transcriptional Regulation In Animalsmentioning
confidence: 99%